Nanoparticles for Modulation of Astrocyte Physiology: A Possible Therapeutic Agent to Control Brain Hyper-Excitability - Barthakur, Manash (New Ideas Concerning Science and Technology Vol. 5, 2021)
Brain hyper-excitability is an abnormal state of the brain that arises due to the burst firing of a neuron. In a normal brain, neuronal activities are modulated by the astrocytes, so, brain hyper-excitability also associated with astrocyte physiology. Scientists believe that the modulation of astrocytes can be an option to control hyperactive brain disorders. Different nano-particles are developed to regulate astrocyte function to control brain hyper-excitability and to prevent brain disorder. Charged nanoparticles are either incorporated in the lipid bi-layer or attached to channel protein present in the plasma membrane to control the membrane potential of the astrocyte. None of the techniques is fully effective till today to control brain hyper-excitability.